The Volcanic Hazards Assessment Support System for the Online Hazard Assessment and Risk Mitigation of Quaternary Volcanoes in the World - Takarada, Shinji (Frontiers in Earth Science, 2017)
Volcanic hazards assessment tools are essential for risk mitigation of volcanic activities. A number of offline volcanic hazard assessment tools have been provided, but in most cases, they require relatively complex installation procedure and usage. This situation causes limited usage of volcanic hazard assessment tools among volcanologists and volcanic hazards communities. In addition, volcanic eruption chronology and detailed database of each volcano in the world are essential key information for volcanic hazard assessment, but most of them are isolated and not connected to and with each other. The Volcanic Hazard Assessment Support System aims to implement a user-friendly, WebGIS-based, open-access online system for potential hazards assessment and risk-mitigation of Quaternary volcanoes in the world. The users can get up-to-date information such as eruption chronology and geophysical monitoring data of a specific volcano using the direct link system to major volcano databases on the system. Currently, the system provides 3 simple, powerful and notable deterministic modelling simulation codes of volcanic processes, such as Energy Cone, Titan2D and Tephra2. The system provides deterministic tools because probabilistic assessment tools are normally much more computationally demanding. By using the volcano hazard assessment system, the area that would be affected by volcanic eruptions in any location near the volcano can be estimated using numerical simulations. The system is being implemented using the ASTER Global DEM covering 2790 Quaternary volcanoes in the world. The system can be used to evaluate volcanic hazards and move this toward risk-potential by overlaying the estimated distribution of volcanic gravity flows or tephra falls on major roads, houses and evacuation areas using the GIS-enabled systems. The system is developed for all users in the world who need volcanic hazards assessment tools.